Pengaruh Bahasa Gaul dalam Komunikasi Generasi Z di Era Perkembangan Digital - Muna, Vicka Naylul (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the influence of slang language on Generation Z’s communication on social media, examining both positive and negative aspects. Slang, as a linguistic adaptation of the Indonesian language, plays a significant role in Generation Z’s daily interactions, especially in the context of social and popular culture. This research employs a literature review method, analyzing 30 scholarly references from 2014 to 2024. Findings reveal that slang strengthens social solidarity and group identity while fostering linguistic creativity. However, it also has negative impacts, such as reduced formal communication skills and potential intergenerational conflicts. Social media acts as a major catalyst for slang dissemination, accelerating the adoption of new terms and linguistic innovation but also increasing social pressure to keep up with trends. The impacts of slang usage are observed in several areas: 1) psychological, which contains mental health conditions that also affect behavior, emotions, and motivation; 2) social environment, which includes how the influence of slang affects character, lifestyle, relationships, and social interactions; and 3) Language use, which includes how generation Z is influenced by slang on the conformity of standard Indonesian.